Strategic Risk Assessment of Hazardous Energetic Chemicals in Defense Supply Chains: A Coupled Risk Framework for Ammonium Perchlorate (AP), RDX, and HMX - Indriani, Sulfi; Yanto, Sri; Putra, I Nengah; Kurniawati, Firdah Dipi Juni (Indonesian Journal of Advanced Research, 2026)
Energetic materials such as ammonium perchlorate (AP), RDX, and HMX are essential in modern defense systems but pose multidimensional risks across industrial supply chains. This study presents a literature-based assessment integrating hazard profiling with node-based risk characteristics; RDX shows high acute process instability, AP poses environmental risks due to perchlorate mobility in groundwater, and HMX presents strategic coupling risk from production interdependence. A Coupled Risk Triangle Model is proposed, framing energetic chemical governance as a dynamic system linking reactive instability, environmental persistence, and strategic supply concentration. The findings indicate that risks extend beyond occupational safety to environmental regulation and national security resilience. Effective mitigation therefore requires lifecyle-integrated governance, supply diversification, and resilience-oriented industrial strategies.